Significance of Morphology in Characterizing Human Health Risk from di(2-ethylhexyl) Phthalate in Polyvinyl Chloride Microplastics in Groundwater - Ki-Han Song; Sang-Gyu Yoon; Jin-Yong Lee; Jinsung An (Toxics)
In this study, a human health risk assessment was performed on the ingestion route of groundwater containing polyvinyl chloride (PVC) microplastics (MPs), and the carcinogenic and non-carcinogenic risks of di(2-ethylhexyl) phthalate (DEHP), a representative additive, were determined. In particular, the impact of volume diversity according to the shape (morphology) of PVC MP (fragment, fiber, film) on the risk characterization was intensively explored. Firstly, a continuous particle size distribution following a power function was derived using the abundance ratio of PVC MPs by size in the investigated groundwater, and human health risk assessment for DEHP in the PVC MPs was performed through the volume distribution according to the shape of MPs. DEHP human health risk assessment showed an excess cancer risk (ECR) of below 10−6 for a 95% cumulative probability for all MP shapes, but the values varied depending on the shape. Sensitivity analysis showed that the parameter that most affected human health risk was MP volume, second to concentration, which is dependent on MP shape. Therefore, it is necessary to consider the variety of MP shapes during human health risk assessment, and it can be achieved through probabilistic risk assessment utilizing the probability distribution for size and shape of MPs.